2018
DOI: 10.3168/jds.2017-13227
|View full text |Cite
|
Sign up to set email alerts
|

Lactation response to soybean meal and rumen-protected methionine supplementation of corn silage-based diets

Abstract: Corn silage, an important forage fed to dairy cows in the United States, is energy rich but protein poor. The objectives of this experiment were to investigate the effects on production of milk and milk components of feeding corn silage-based diets with 4 levels of dietary crude protein (CP) plus rumen-protected methionine (RPM). Thirty-six cows were blocked by days in milk into 9 squares and randomly assigned to 9 balanced 4 × 4 Latin squares with four 4-wk periods. All diets were formulated to contain, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
4
19
1
Order By: Relevance
“…The levels of essential AA and crude protein in the diets significantly affect dry matter intake. These are also affected when there is a large difference between the AA level in feed and the amount of AA required by the animal [ 12 , 23 26 ]. It is notable that a significant proportion of corn grain was used as a source of feed ingredient in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of essential AA and crude protein in the diets significantly affect dry matter intake. These are also affected when there is a large difference between the AA level in feed and the amount of AA required by the animal [ 12 , 23 26 ]. It is notable that a significant proportion of corn grain was used as a source of feed ingredient in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Methionine [ 3 , 7 ] and lysine [ 8 , 9 ] are widely known as first-limiting AAs, which affect the milk production and milk protein of dairy cows under many dietary regimes. In addition, lysine and methionine have long been regarded as potentially rate-limiting factors for milk production, either alone or in combination [ 6 , 10 12 ]. The production responses to dairy cows can be greater when methionine, used in combination with lysine, is directed into the small intestine and bloodstream [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was a trend for lower SNF with decreased CP feeding and RPM supplementation (P = 0.09). [19], from 13-17% [9]. Moreover, several trials have demonstrated that with RPM supplementation, milk yield [10,20] and milk protein yield [21] increased.…”
Section: Milk Yield and Milk Compositionmentioning
confidence: 99%
“…Recently years, there have been some research that explored the effects of rumenprotected methionine (RPM) supplementation on dairy cows. Several studies indicated that RPM supplementation and decreasing dietary CP could increase milk production, milk protein, fat as well as lactose contents [7][8][9][10]. Recently research has shown that an increase in overall dry matter intake (DMI) could be found after parturition when cows fed lower dietary CP and RPM [11].…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency of protein utilization (the proportion of CP consumed that is recovered in milk protein) in dairy cattle ranges between 18 to 19 (Penner et al, 2009;Rhoads et al, 2009) and 42 to 44% (Nursoy et al, 2018;Nichols et al, 2019). Differences in efficiency of protein utilization also seem to be affected by the level of production.…”
Section: Metabolic Partitioningmentioning
confidence: 99%